Application of Glucagon and Glucagon-Like Peptide Agonists in Disease Treatment - Guo, Jinqi; Hu, Haibin (Transactions on Materials, Biotechnology and Life Sciences, 2024)
With the continuous advancement of medical technology, glucagon has been confirmed to be closely related to many diseases, such as diabetes, glucagonoma cell hyperplasia and neoplasm (GCHN), hepatitis and neurological diseases, which take numerous life each year. The identification of several diseases, like Mahvash syndrome as an autosomal recessive inherited pancreatic neuroendocrine tumor syndrome associated with GCGR inactivation mutations deepens our understanding of GCG signal pathway. As disease mechanisms are better understood, more novel drugs are being developed to treat these diseases. Glucagon-like peptide agonists, such as cotadutide, are shown to possess neuroprotective properties in the context of neurodegenerative diseases, also exhibits potential in ameliorating blood glucose control, weight management, and liver fat reduction, offering a promising avenue for developing novel treatments. The linkage between GCHN and GCGR gene inactivation highlights the potential role of GCGR in tumorigenesis, emphasizing its relevance in oncological research. In summary, these findings provide comprehensive insights into neuroprotection, metabolic regulation, genetic disorders, and oncology, offering a holistic view of the potential implications of these entities in various medical contexts.